A Hybrid Density Network-Based Dance Movement Generation Algorithm and Internet of Things for Young Children. (20th September 2022) - Fang, Yuting
Abstract : The music development matching model and the quantifiable planning model have an undesirable fit between the dance produced by the model and the music self in terms of music-driven dance development age (e.g., generated dance development is lacking, and long-distance dance arrangements are lacking in perfection and discernment). The traditional methodology cannot produce new dance moves or other associated concerns. To address these concerns, we are working on a dance age estimation based on technological developments and neural networks that will eliminate the need for voice and development planning. The first stage uses the prosody elements and sound beat highlights extracted from music as music highlights, while the second stage uses the directions of essential human body issues derived from dance recordings as movement highlights. The model's generating module acknowledges the vital planning of music and dance advancements to build a smooth dance posture in the next stage; the discriminator module acknowledges the autoencoder module agent has improved sound characteristics and the consistency of dance and music. In the third and final step, the model's transformed form changes the dance act succession into a good diversity of dance. Finally, a reasonable rendition of the dance that matches the music has been found (e.g., trial data is gathered from online dance recordings, and the exploratory outcomes are examined from five perspectives: poor work esteem, correlation of various baselines, assessment of grouping age influence, client examination, and genuine dance recording quality assessment). The proposed dance age model has a reasonable impact on converting into actual dance recordings, according to the results.